2018
DOI: 10.1017/s0022109017001193
|View full text |Cite
|
Sign up to set email alerts
|

Short Covering Trades

Abstract: Short sellers are known to have private information about security prices. Empirical evidence of short selling, however, is based on only half of short sellers’ trading activity; specifically, the opening of the position. Using disclosed large-short-position data from the Japanese stock market, we provide the first detailed evidence of covering trades and find a positive reaction to short covering that only partially reverses. Although these results are consistent with substantial transaction costs for closing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Finally, making use of the publicly disclosed short selling positions, Greppmair et al (2020) indicate that short sellers adapted quickly upon the onset of the pandemic, since short selling activity shifted towards companies with low financial flexibility and in countries with limited fiscal space, a profitable strategy. This confirms that short sellers were quick to incorporate complex information during market stress period, either from their ability to process available information (Engelberg et al, 2012;Reed, 2013), or with the help of potential private information (Boehmer et al, 2018(Boehmer et al, , 2020. Indirectly, this confirms the findings of our descriptive analysis in Appendix 2 on the displacement effect, namely that no material changes of NSPs took place from banning to non-banning jurisdictions during the bans period.…”
supporting
confidence: 77%
“…Finally, making use of the publicly disclosed short selling positions, Greppmair et al (2020) indicate that short sellers adapted quickly upon the onset of the pandemic, since short selling activity shifted towards companies with low financial flexibility and in countries with limited fiscal space, a profitable strategy. This confirms that short sellers were quick to incorporate complex information during market stress period, either from their ability to process available information (Engelberg et al, 2012;Reed, 2013), or with the help of potential private information (Boehmer et al, 2018(Boehmer et al, , 2020. Indirectly, this confirms the findings of our descriptive analysis in Appendix 2 on the displacement effect, namely that no material changes of NSPs took place from banning to non-banning jurisdictions during the bans period.…”
supporting
confidence: 77%
“…Next, we verify the role of informed trading for the relationship between common short selling and excess comovement. Studies have shown that short sellers are sophisticated market agents, who trade on superior information and are able to predict future stock price movements (Boehmer et al, 2008, Diether et al, 2009b, Boehmer et al, 2018. By shorting several stocks, short sellers expect future price declines.…”
Section: Introductionmentioning
confidence: 99%
“…We contribute to a growing body of literature that makes use of short selling disclosure data (Boehmer et al, 2018, Jones et al, 2016. Previous studies have used this data to analyse the behaviour of short sellers and the relation between short positions and underlying stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…Previously available equity lending information is consolidated across all short positions in the stock. To assess differences across the short positions in a stock,Jank and Smajlbegovic (2021) andBoehmer et al (2018) examine mandatory disclosures of large short positions in Europe and Japan, respectively, while vonBeschwitz et al (2022) andChoi, Park, Pearson, and Sandy (2020) study hedge fund trades.…”
mentioning
confidence: 99%